Synthesis of hollow forsterite by coating method and study of its dielectric properties - Asghar, Ghulam; Dong, Xue; Chae, Sudong; Yoo, Chan Sei; Oh, Seungbae; Choi, Kyung Hwan; Jeon, Jiho; Woo, Chaeheon; Kim, Tae Yeong; Ahn, Jungyoon; Oh, Hyung Suk; Yu, Hak Ki; et al. (Ceramics International, 2023)
Wireless communication technologies are operating at higher frequencies in the current ubiquitous age, dielectrics with low dielectric constant and low dielectric loss are highly desired. A novel coating method was used for the synthesis of hollow forsterite ceramics. Here, magnesium glycolate with relatively high and high specific surface area (243.44 m2/g) and pore width (1.35 nm) is used as core material. Highly pure uniform-sized forsterite phases were obtained at a low calcination temperature of 900 °C/2 h. Scanning electron microscope, Transmission electron microscope, and X-ray diffraction were used to characterize the morphology and phase development at different calcination temperatures. The dielectric properties were measured in the range of microwave frequencies. As prepared, forsterite (Mg2SiO4) ceramics had shown excellent dielectric properties with εr = 1.85 and dielectric loss = 0.007 at 1 GHz. As wave propagation delay and attenuation depend on dielectric constant and dielectric loss. This ultra-low εr of 1.85 will enhance the signal speed in the microwave frequencies region which makes forsterite a promising candidate for electronics packaging applications.
Keywords: current; Calcination temperature; Ceramic coating method; Coating methods; Dielectrics property; Forsterites; High frequency HF; Low dielectric constant dielectrics; Sintering process; Wireless communication technology; Ceramics coating method; Dielectric constant; Forsterite; Sintering process